Amphitremida (Poche, 1913) Is a New Major, Ubiquitous Labyrinthulomycete Clade - Gomaa, Fatma; Mitchell, Edward; Lara, Enrique (My University, 2013)
Micro-eukaryotic diversity is poorly documented at all taxonomic levels and the phylogenetic affiliation of many taxa - including many well-known and common organisms - remains unknown. Among these incertae sedis taxa are Archerella flavum (Loeblich and Tappan, 1961) and Amphitrema wrightianum (Archer, 1869) (Amphitremidae), two filose testate amoebae commonly found in Sphagnum peatlands. To clarify their phylogenetic position, we amplified and sequenced the SSU rRNA gene obtained from four independent DNA extractions of A. flavum and three independent DNA extractions of A. wrightianum. Our molecular data demonstrate that genera Archerella and Amphitrema form a fully supported deep-branching clade within the Labyrinthulomycetes (Stramenopiles), together with Diplophrys sp. (ATCC50360) and several environmental clones obtained from a wide range of environments. This newly described clade we named Amphitremida is diverse genetically, ecologically and physiologically. Our phylogenetic analysis suggests that osmotrophic species evolved most likely from phagotrophic ancestors and that the bothrosome, an organelle that produces cytoplasmic networks used for attachment to the substratum and to absorb nutrients from the environments, appeared lately in labyrithulomycete evolution.